Segmental odontomaxillary dysplasia - Arti Agrawal; Jonathan Daniel; Vasudevan Vijeev (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2014)
Segmental odontomaxillary dysplasia is a type of hemi-maxillofacial dysplasia. It is a sporadic, mesoectodermal dysplasia that presents early in life, possibly as early as in utero and exhibits male gender predominance (1.7:1.0). Its features include enlargement of the soft tissue and/or bone of one hemimaxilla that may produce mild facial asymmetry, sclerotic radiographic bone changes and dental developmental abnormalities. The dense bone, which often exhibits a radiographic vertical orientation of the trabecular bone pattern, is generally associated with delayed eruption of the teeth. Congenitally missing premolar teeth (eithe or both) is a common feature of this condition that is of significant diagnostic value. Ipsilateral cutaneous findings have been reported in 23% of cases. Immature woven bone forming irregular patterns are seen histologically. Herein, we present a case report on segmental odontomaxillary dysplasia in a 13-year-old boy.